2010
DOI: 10.1109/tuffc.2010.1600
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying viscoelasticity of gelatin phantoms by measuring impulse response using compact optical sensors [Correspondence]

Abstract: Tissue elastography measures tissue mechanical properties, which contain important physiological information and help medical diagnosis. Instead of tracking shear wave propagation inside tissue as do magnetic resonance elastography and ultrasound based techniques, this study focuses on monitoring the propagation of surface Raleigh waves stimulated by short impulses. The method is noncontact, noninvasive, and low cost and has a potential for clinical applications. A customized device designed to measure surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…The Young moduli presented in table 2 are estimates obtained from averaged phase-velocity values, using values for the Poisson ratio and density that were found in the literature. However, the standard deviations of the phase velocities were less than 1 m s 21 and of the Young modulus were less than 2.5 kPa, which is small compared with the expected stiffness changes that are found in skin diseases, e.g. basal cell carcinoma tumours are 3 -50% stiffer compared with healthy skin [4,16,41].…”
Section: Measurements and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Young moduli presented in table 2 are estimates obtained from averaged phase-velocity values, using values for the Poisson ratio and density that were found in the literature. However, the standard deviations of the phase velocities were less than 1 m s 21 and of the Young modulus were less than 2.5 kPa, which is small compared with the expected stiffness changes that are found in skin diseases, e.g. basal cell carcinoma tumours are 3 -50% stiffer compared with healthy skin [4,16,41].…”
Section: Measurements and Resultsmentioning
confidence: 99%
“…This wave is rich in frequency content, which enables the determination of the mechanical properties of different skin layers within a single measurement and analysis. Previous studies [21,22] have suggested that measuring surface waves with both a laser displacement sensor and low-coherence interferometry is highly sensitive to the shape of the tissue surface. Therefore, it has been difficult to determine the skin properties because the skin is rough, and has curvatures [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have verified our surface wave method by different techniques, for example, an ultrasound and laser vibrometer technique [25], a laser displacement sensor method [34], and comparison of ultrasound technique and indentation technique [35]. The repeatability of our measurements on human skin is tested by repeating five measurements at the same site on the forearm of a healthy volunteer.…”
Section: Discussionmentioning
confidence: 96%
“…Another approach taken by others has been to directly estimate the frequency-dependent surface (Rayleigh) wave speed from experimental data and then to optimize the coefficients in an assumed viscoelastic model type to minimize the difference between the measured and predicted values of wave speed. 3,[20][21][22] In an analogous manner, shear wave speed dispersion derived from elastography techniques has been used to estimate the shear viscoelasticity with an assumed viscoelastic model type. [23][24][25][26][27][28][29] In the present article, the relative merits of these approaches are explored theoretically, computationally, and experimentally.…”
Section: Introductionmentioning
confidence: 99%